The Effect of Pandemic on Shilpgram of Patna, Bihar - Dr. Richa Jagatramka,; Ar. Raunak Prasad,; Shreesh Thakur, (RES MILITARIS, 2022)
Handicraft have always been a vital part of our rich culture incorporating various folklore, locally available raw material, it acts as source of income for a large population of landless and poor. Handicraft sector has seen multiple rise and downfall in market demand and needs through the years. The effect of the recent pandemic has led to a loss in the handicraft sector too. The handicraft development in the country was only significantly improving but the recent pandemic has created a larger gap between the crafts people and the market. The study is based on the effects of pandemic on the craftsmen in Shilpgram, with respect to the procurement of raw material, process, and generation of new designs. The methodology used for the study is based on indirect participative interviews and physical survey of the crafts and their designs available in the Shilpgram in Patna city. The study illustrates that the states like Bihar having a single craft centre in capital city Patna, which was completely shut since the lockdown is leading the craftsmen to discontinue the craft and look for alternative works. The conclusion also discusses various recommendations for the sustenance of the crafts and craftspeople.